British American Tobacco: Building A Better Tomorrow - Mahmood, Kashif; Zia ud din, Muhammad; Liaqat, Ayesha (Advances in Social Sciences Research Journal, 2022)
A multinational company associated with the manufacturing and selling business of cigarettes, raw tobacco and other oral nicotine products since 1902. Based on net sales BAT is the largest cigarettes manufacturing company worldwide and have headquarter at London, England. With multiple brands including Pall Mall, Lucky Strike, Dunhill & Kent, BAT has operations in 180 countries. New product Vype, Vuse, Glo and Velo are also introduced. In March 2020 BAT Group sets an inspirational drive for the business and company by presenting its progressed strategy. The BAT’s transformed purpose to “build a better tomorrow” by reducing the health effect of its commercial business activity with donating a greater choice of reduced risk and enjoyable products for its consumers. It is to develop its growth model by the developing a portfolio in nicotine and beyond, meeting evolving needs of customer for satisfaction and enjoyment.